A study on the Prevalence and Determinants of Health-Related Quality of Life in Women diagnosed with Hypertension - Kaur, Ramandeep; Sekhon, Charan Kamal; Airi, Monika; Chaudhary, Anurag; Sharma, Pranjl (Indian Journal of Community Health, 2025)
Introduction: Health-Related Quality of Life (HRQoL) is negatively affected by hypertension, which highlights the significance of efficient disease management. Aim & Objective: This study assessed the Quality of Life in hypertensive women, comparing those with controlled and uncontrolled blood pressure. Methods and Material: The study was designed using the WHO stepwise strategy for NCD surveillance (STEPS) to give prevalence estimates of risk factors for hypertension in three age categories (18-29, 30-44, and 45-69 years). Results: A total of 2160 females were screened for hypertension. 827 (38.27%) were found to be hypertensive, with 27.9% in stage 1 and 10.4% in stage 2 HTN. The MINICHAL score was used to measure HRQOL, and the average scores in the somatic and mental categories were 1.10 ± 2.15 and 4.76 ± 4.84, with an overall average total score of 5.99 ± 6.13. The somatic domain of the MINICHAL scale shows statistically significant positive relationship, with an Exp (B) of 1.101, indicating that for each unit increase in this domain, the odds of the outcome increase by approximately 10.1%. Conclusions: The MINICHAL-based HRQOL assessment showed that ages 45–69 had higher scores, indicating greater risk of adverse health outcomes.